Conhecimento indígena e o processo de formação social do jovem no contexto da Comunidade Maruwai, Terra Indígena São Marcos – Roraima - Andrade, Edite da Silva (Universidade Federal de Roraima, 2022)
In the present study, I researched indigenous knowledge and social formation of the young in the context of Maruwai community T.I. San Marcos. We started from the need to understand the processes that occur with indigenous youth in a context of significant changes due to contact with the school, with churches and religions and other elements that have modified forms of preparation for adult life. Faced with these conflicts and cultural changes, we seek to identify which own knowledges are transmitted to young people in the context of family, community and which involve social values, visions of the life and of the world. In this research, we used the idea of a collaborative ethnography, concurrent with the proposal of the intercultural inductive method and the theory of activity. Thus, we developed this study to understand and to explicit the implicit knowledges in the meaningful activities which young people participate. In Vygotskian perspective (theory of activity), we start from the reality of these residents to understand their conceptions of work and world, as well as access the indigenous knowledges. The analyzed activities were highlighted by the socionatural calendar, in which the relationship between society and nature is understood as an integral part of indigenous education. We note that the preparation of young people give up the need that community life requires. There are knowledges that are specific of their realities and are transmitted to their children through orality, the experience in practice, such as in the case of dances, songs, of the stories and their beliefs. The acquisition of these knowledges by new members is by observation and "learning by doing". In this perspective, the time, the space and the environment are part of this understanding. It is in this interaction of respect with nature, that these residents from Maruwai pass on social values and improve them to meet their own needs.